New MPPT algorithm for PV applications based on hybrid dynamical approach. (December 2016) - Elmetennani, S.; Laleg-Kirati, T.M.; Djemai, M.; Tadjine, M.
Abstract : Highlights: A photovoltaic chain is modeled as a hybrid system. A hybrid automata is designed to optimize the PV chain. The hybrid algorithm is efficient under varying working conditions. It has been validated numerically and experimentally. Abstract: This paper proposes a new Maximum Power Point Tracking (MPPT) algorithm for photovoltaic applications using the multicellular converter as a stage of power adaptation. The proposed MPPT technique has been designed using a hybrid dynamical approach to model the photovoltaic generator. The hybrid dynamical theory has been applied taking advantage of the particular topology of the multicellular converter. Then, a hybrid automata has been established to optimize the power production. The maximization of the produced solar energy is achieved by switching between the different operative modes of the hybrid automata, which is conditioned by some invariance and transition conditions. These conditions have been validated by simulation tests under different conditions of temperature and irradiance. Moreover, the performance of the proposed algorithm has been then evaluated by comparison with standard MPPT techniques numerically and by experimental tests under varying external working conditions. The results have shown the interesting features that the hybrid MPPT technique presents in terms of performance and simplicity for real time implementation.